THE EFFECT OF THE GROUP COUNSELING SERVICE WITH SOCIODRAMA’S TECHNIQUE TOWARD STUDENTS EMPATHY CLASS X SMA N 9 OF BENGKULU CITY - Muslimatun, Anis; Makmurtomo, Agus (UNIB Press, 2019)
ABSTRACTThe purpose of this study was to determine the effect of group counseling services with sociodrama’s technique toward student empathy class X SMA N 9 Bengkulu city. This research is a quasi experimental research design with nonequivalent control group. The population in this study is a tenth grade student of SMAN 9 Bengkulu city. The sample was determined by sampling purposive in order to obtain the group will be group counseling services. The methods of data collection using pre-test and post-test form 47 item questionnaire empathy. Data from this study were analyzed using anova mix test. Based on the analysis the results showed that (1) The average score of students' pre-test experimental group was 154,80 and the average score of the control group students was 163,30. While the average score of post-test the experimental group students of 190,60 and an average score of 169,70 for the control group students. This result suggests that empathy scores students of experimental group is better than the students control group empathy scores. (2) In the experimental group Mean Difference (MD) value of -35,80 was significant of 0,00 (P<0,05) and in the control group Mean Difference (MD) value of -7,90 with significant 1,88 (P> 0,05). This shows that the experimental group had increased student empathy significant and in the control group had increased the student empathy but not signitifikan. (3) The results of anova mix test with a significance value of 0,001 (P<0,05). This result shows that there is a differents student empathy of the group with technique sosiodrama’s guidance services sociodrama’s against student empathy between the control group and the experimental group. (4) In the score of eta squared donations increase empathy using group counseling services with sociodrama’s techniques in the experimental group amounted to 75,5% and in the control group by 13%. Keywords: Group Counseling, Students Empathy and Sociodrama’s Technique